Experimental & simulation study of 16kWp photovoltaic (PV) system performance & the investigation of PV heat island effect - Devihosur, Shiddalingeshwar Channabasappa (Nanyang Technological University, 2022)
This dissertation documents the experimental and simulation investigation of a 16kWp solar photovoltaics (PV) system’s (located in SIT@Dover) performance along with the investigation of the urban heat island (UHI) effect resulting from the PV system. An existing 16kWp solar PV system in SIT@Dover comprises of two plots (Plot A and B). Each plot consists of two strings with 10 x 400W solar panels for each string. Each solar module is 2m^2. The effective coverage of the PV system is 80m^2. The FusionSolar web platform is used to log and store various power, energy, and sensor data from the PV system. Two weather stations are installed in SIT@Dover: one in the vicinity of the PV system and another on a building rooftop. The PVSyst simulation software (version 7.2) was used to replicate and simulate the physical PV system in SIT@Dover to compare the PV yield and performance indicators data with the actual field data. PVSyst simulations were run to quantify the effectiveness of the PV optimizers in the SIT@Dover setup. Simulations were conducted to ascertain the losses due to the presence of building shade. Temperature sensors were installed above three different surfaces to quantify the temperature differences of the heat emitted. The energy yield, performance ratio (PR) and efficiency of the PV system from FusionSolar were compared with PVSyst simulation data from Aug 2021 – Feb 2022. The percentage yield variance between the two was found to be 3.22 - 37.26%. Generally, the large differences were attributed to a dissimilar weather data input from the PVSyst meteo file and the true weather data. The disparity in performance ratio (PR) was seen to be largely within an acceptable range of 2.77-5.22% with the exception of the Jan 2022 where the difference was 10.38%. The differences in efficiency were found to be minimal at 0.12-1.90%. Simulation results from PVSyst revealed that the presence of surrounding buildings in SIT@Dover caused an annual energy yield loss, PR loss, efficiency loss of 9.38% (or 1857 kWh), 7.10% and 1.41% respectively. The inclusion of power optimizers at the SIT@Dover PV system had insignificant annual energy yield, PR, and efficiency gains of 1.48%, 1.10% and 0.22% respectively, rendering the power optimizers ineffective in providing significant benefits in performance gain of the PV system. A numerical analysis to comprehend the extent of the PV heat island effect (PVHIE) was conducted. The clear day 24-h mean temperature data revealed that the PV system elevated the air temperature directly above it by 2.97 °C in comparison to the ambient temperature. On the same day with the overhead sun between 1200 – 1400hrs, the PVHIE effects were accentuated at 13°C above the ambient temperature. A regression technique known as Analysis of Variance (ANOVA) was used to derive a multi-variate linear equation to predict the solar module temperature on Plot A and the temperature from the PVHIE. The R2 values resulting from the validation of the two equations were found to be more than 0.90. The two equations were tested and validated with test data. The mean discrepancy between the actual and calculated module temperature was found to be 1.76°C while the mean variation between the actual and calculated PV heat island effect temperature was 1.67°C. The two linear equations are presented as follows: